2021
DOI: 10.3934/mbe.2021440
|View full text |Cite
|
Sign up to set email alerts
|

A deep bidirectional recurrent neural network for identification of SARS-CoV-2 from viral genome sequences

Abstract: <abstract> <p>In this work, Deep Bidirectional Recurrent Neural Networks (BRNNs) models were implemented based on both Long Short-Term Memory (LSTM) and Gated Recurrent Unit (GRU) cells in order to distinguish between genome sequence of SARS-CoV-2 and other Corona Virus strains such as SARS-CoV and MERS-CoV, Common Cold and other Acute Respiratory Infection (ARI) viruses. An investigation of the hyper-parameters including the optimizer type and the number of unit cells, was also performed to att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Commonly used metrics are employed in the proposed study to evaluate the performance and prediction errors of the proposed models. These metrics include the square of the correlation coefficient R 2 [59,60] and the RMSE [61]. The values of both metrics yield a good indication of the accuracy and prediction capability of the proposed models and allow us to select the most efficient model for the prediction of wear rates of UHMWPE.…”
Section: Multiobjective Grey Wolf Optimizermentioning
confidence: 99%
“…Commonly used metrics are employed in the proposed study to evaluate the performance and prediction errors of the proposed models. These metrics include the square of the correlation coefficient R 2 [59,60] and the RMSE [61]. The values of both metrics yield a good indication of the accuracy and prediction capability of the proposed models and allow us to select the most efficient model for the prediction of wear rates of UHMWPE.…”
Section: Multiobjective Grey Wolf Optimizermentioning
confidence: 99%
“…The input is routed across the network layers during the forward phase when training a CNN [ 19 , 41 , 42 ]. Gradients are back-propagated and neuron weights are updated during the backward phase.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Chen et al [ 20 ] and Zou et al [ 21 ] reported different ensemble methods based on the CNN and long short-term memory (LSTM) to predict the human N6-methyladenosine sites from mRNA sequences. Deif et al [ 22 ] came up with a deep bidirectional recurrent neural networks (BRNNs) model that combined with LSTM and GRU to distinguish between the genome sequence of SARS-CoV-2 and other coronavirus strains. Kumar et al [ 23 ] constructed two models for predicting COVID-19 by using modified LSTM and reinforcement learning algorithms.…”
Section: Introductionmentioning
confidence: 99%